Co-expression in CHO cells of two muscle proteins involved in excitation-contraction coupling - Takekura, Hiroaki; Takeshima, Hiroshi; Nishimura, Seiichiro; Takahashi, Masami; Tanabe, Tsutomu; Flockerzi, Veit; Hofmann, Franz; Franzini-Armstrong, Clara (Journal of muscle research and cell motility, 1995)
Ryanodine receptors and dihydropyridine receptors are located opposite each other at the junctions between sarcoplasmic reticulum and either the surface membrane or the transverse tubules in skeletal muscle. Ryanodine receptors are the calcium release channels of the sarcoplasmic reticulum and their cytoplasmic domains form the feet, connecting sarcoplasmic reticulum to transverse tubules. Dihydropyridine receptors are L-type calcium channels that act as the voltage sensors of excitation-contraction coupling: they sense surface membrane and tranverse tubule depolarization and induce opening of the sarcoplasmic reticulum release channels. In skeletal muscle, ryanodine receptors are arranged in extensive arrays and dihydropyridine receptors are grouped into tetrads, which in turn are associated with the four subunits of ryanodine receptors. The disposition allows for a direct interaction between the two sets of molecules.